Dental students’ interaction with clinical instructors: students’ perspective and dental school’s administrator dean’s response/ Nagham Mohammed Abdullah Al-Jaf... [et al.] - Nagham Mohammed Abdullah, Al-Jaf; Md Sabri, Budi Aslinie; Fadly Loo, Muhamad Faizran Looszen; Ahmad Shaifuddin, Ahmad Aizat (Faculty of Dentistry, 2017)
To evaluate the impact of the clinical instructor communication on dental students’ clinical training in Faculty of Dentistry, Universiti Teknologi Mara (UiTM). A sample of 174 undergraduate clinical dental students were recruited to complete the Clinical Education Instructional Quality Questionnaire (ClinEd IQ) which consists of forty-five questions, forty-three multiple choice questions and two open-ended. The multiple-choice questions consist of 3 subscales which were measured on a six-point Likert Scale from “strongly disagree” to “strongly agree”. The open-ended responses were analysed using thematic analysis. This paper discusses the Subscale of interaction with clinical instructors and the open-ended responses. The responses of 150 students were evaluated. The students rated their interaction with instructors with a mean score of 4.64 on a six -point scale. There was a significant difference between mean scores for each academic level with year five students’ score being highest. There were four areas of concern identified through the open-ended responses. While the quality of supervision in terms of interaction with clinical instructors is considered satisfactory and the students generally reported positive experiences, there is room for improvements especially regarding areas of concern.